Coupling of NMDA receptors and TRPM4 guides discovery of unconventional neuroprotectants - Yan, Jing; Bengtson, C. Peter; Buchthal, Bettina; Hertle, Anna M.; Bading, Hilmar (Science. First release, 2020)
Interface targeting skirts excitotoxicity - Nearly all attempts to use traditional N-methyl-d-aspartate receptor (NMDAR) antagonists to treat neurodegenerative diseases have failed. This is because NMDARs are not only promoters of neuronal death but also have essential physiological roles in synaptic plasticity and cognitive functions such as learning and memory. Yan et al. explored the structural basis of NMDAR coupling to neuronal cell death (see the Perspective by Jones). The death-promoting activity, but not the essential physiological function, was mediated by the physical interaction of NMDARs with TRPM4, a calcium-impermeable ion channel activated by intracellular calcium, depolarization, and temperature. A subsequent structure-based computational drug screen led to the discovery of neuroprotective small molecules that block the NMDAR-TRPM4 interaction interface but spare the critical healthy NMDAR function. - Science, this issue p. eaay3302; see also p. 168 - Structured Abstract - INTRODUCTIONN-methyl-d-aspartate receptors (NMDARs) are glutamate-gated, calcium-permeable neurotransmitter receptors. They are fundamental to brain development, they control synaptic plasticity in the adult, and they initiate transcriptional responses needed for the consolidation of adaptive processes in the nervous system such as memory and acquired neuroprotection. However, NMDARs are also potentially harmful to neurons because they can initiate transcription shutoff pathways and can lead to mitochondrial dysfunction and even to excitotoxic cell death induced by excessive glutamate. The molecular basis of toxic NMDAR signaling is unknown, although a high intracellular calcium load has been implicated. An alternative model suggests that, depending on their location (synaptic versus extrasynaptic), NMDARs can either promote neuronal survival or cause cell death. - RATIONALEWe hypothesized that NMDARs acquire toxic features through physical interaction with one or more other proteins that may be present at extrasynaptic but not synaptic locations. Identification of NMDAR-associated proteins and the mapping of their respective interaction domains may enable the development of innovative means to disrupt a putative death signaling complex. In particular, the search for interaction interface inhibitors could yield novel compounds that—unlike classical NMDAR blockers—would bring about neuroprotection by stripping off the toxic component of extrasynaptic NMDAR signaling without compromising the physiological functions of synaptic NMDARs. - RESULTSWe found that the NMDAR subunits GluN2A and GluN2B form a complex with transient receptor potential cation channel subfamily M member 4 (TRPM4). The NMDAR/TRPM4 interaction is mediated by a 57-amino acid intracellular domain of TRPM4, termed TwinF, that is positioned just beneath the plasma membrane. TwinF interacts with I4, an evolutionarily highly conserved stretch of 18 amino acids with four regularly spaced isoleucines located within the intracellular, near-membrane portion of GluN2A and GluN2B. The NMDAR/TRPM4 complex can be disrupted by (i) expression of TwinF, which acts by competing with endogenous TRPM4 for binding to GluN2A and GluN2B, or (ii) small-molecule NMDAR/TRPM4 interaction interface inhibitors that we identified with a TwinF structure-based computational compound screen. Both TwinF and the small-molecule interface inhibitors provide robust protection against excitotoxic cell death in cultured neurons and in vivo in mouse models of neurodegeneration. They also eliminate excitotoxicity-associated transcription shutoff and mitochondrial dysfunction while leaving synaptic and extrasynaptic NMDAR-mediated currents and calcium signaling unaffected. - CONCLUSIONOur study uncovered the requirement of an NMDAR/TRPM4 complex for excitotoxicity. According to proteomics databases for synaptic proteins from mouse and human cortex and hippocampus, TRPM4 is absent from the synapse. This indicates that the NMDAR/TRPM4 complex forms extrasynaptically, which explains why extrasynaptic but not synaptic NMDARs promote death signaling. Our findings provide a conceptually new basis for therapeutic targeting of toxic NMDAR signaling, which contributes to the pathology of many neurological conditions including stroke, traumatic brain injury, Alzheimer’s disease, Huntington’s disease, amyotrophic lateral sclerosis, and retinal degeneration. Recombinant and small-molecule NMDAR/TRPM4 interaction interface inhibitors define a class of potent neuroprotectants with a new mode of action that renders extrasynaptic NMDARs nontoxic and eliminates their transcription shutoff signaling. Given that increased toxic signaling of extrasynaptic NMDARs is a pathomechanism shared by many neurodegenerative disorders, NMDAR/TRPM4 interaction interface inhibitors may be effective, broadly applicable therapeutics. Download high-res image Open in new tab Download Powerpoint NMDAR/TRPM4 complex formation is required for excitotoxicity.The NMDAR/TRPM4 complex is responsible for excitotoxic damage induced by excessive glutamate. Mitochondrial dysfunction, neuronal death, and stroke-induced brain damage are schematically illustrated; ΔΨm, mitochondrial membrane potential. A structure-based compound screen using TwinF, the interface of TRPM4 in complex formation, led to the discovery of NMDAR/TRPM4 (N/T) interaction interface inhibitors, which disrupt the N/T complex and prevent excitotoxicity.BRAIN ILLUSTRATIONS: BIORENDER.COM; GRAPHIC: N. CARY/SCIENCE - Excitotoxicity induced by NMDA receptors (NMDARs) is thought to be intimately linked to high intracellular calcium load. Unexpectedly, NMDAR-mediated toxicity can be eliminated without affecting NMDAR-induced calcium signals. Instead, excitotoxicity requires physical coupling of NMDARs to TRPM4. This interaction is mediated by intracellular domains located in the near-membrane portions of the receptors. Structure-based computational drug screening using the interaction interface of TRPM4 in complex with NMDARs identified small molecules that spare NMDAR-induced calcium signaling but disrupt the NMDAR/TRPM4 complex. These interaction interface inhibitors strongly reduce NMDA-triggered toxicity and mitochondrial dysfunction, abolish cyclic adenosine monophosphate-responsive element-binding protein (CREB) shutoff, boost gene induction, and reduce neuronal loss in mouse models of stroke and retinal degeneration. Recombinant or small-molecule NMDAR/TRPM4 interface inhibitors may mitigate currently untreatable human neurodegenerative diseases. - Neuroprotectants are identified that can eliminate toxic activity of NMDA receptors but spare their physiological signaling functions. - Neuroprotectants are identified that can eliminate toxic activity of NMDA receptors but spare their physiological signaling functions.
Gesehen am 14.12.2020